QARAQALPAQ NAQÍL-MAQALLARÍNDA ÚY HAYWANLARÍ ATAMALARÍNÍŃ (TÚYE) QOLLANÍLÍWÍ - Dilanov, Bekmurza Gulimbetovich (SCIENCE and SOCIETY, 2026)
The article examined animal terms used in Karakalpak proverbs and sayings from a linguocultural perspective. By studying paremiological units, we obtain a lot of information about the life, lifestyle, culture, and vocabulary of the Karakalpaks. Because proverbs and sayings contain words related to the original vocabulary of the people.